express y=-3(x+1)^2-5 in standard form?

4 Answers

Relevance
  • Pope
    Lv 7
    4 weeks ago

    The expression "standard form" is a bit loaded. This is what I would call standard form for that parabola equation:

    y = -3(x + 1)² - 5

    -3(x + 1)² - 5 = y

    -3(x + 1)² = y + 5

    (x + 1)² = -1/3(y + 5) ... standard form

    The curve has these parameters:

    Vertex: (-1, -5)

    Axis: x = -1

    Latus rectum: 1/3

    Downward concavity

  • 1 month ago

     y = -3(x + 1)^2 - 5 

     y = -3x^2 - 6x - 8

  • David
    Lv 7
    1 month ago

    If you mean: y = -3(x+1)^2 -5 then y = -3x^2 -6x -8

  • Bryce
    Lv 7
    1 month ago

    y= -3x² -6x -8       

Still have questions? Get your answers by asking now.